2011
DOI: 10.1093/rfs/hhq131
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Management and Corporate Investment During a Financial Crisis

Abstract: . We thank CFO Magazine for helping us conduct the surveys, though we note that our analysis and conclusions do not necessarily reflect those of CFO. We thank Benjamin Ee and Hyunseob Kim for excellent research assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
250
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(273 citation statements)
references
References 19 publications
(35 reference statements)
14
250
1
8
Order By: Relevance
“…Beberapa penelitian menunjukkan peningkatan cash holding saat periode krisis dibandingkan dengan periode non krisis. Campello et al (2011) Hipotesis 1: Perusahaan-perusahaan di Indonesia memegang kas lebih banyak saat krisis keuangan global daripada periode non krisis.…”
Section: Tinjauan Literatur Dan Pengembangan Hipotesisunclassified
See 1 more Smart Citation
“…Beberapa penelitian menunjukkan peningkatan cash holding saat periode krisis dibandingkan dengan periode non krisis. Campello et al (2011) Hipotesis 1: Perusahaan-perusahaan di Indonesia memegang kas lebih banyak saat krisis keuangan global daripada periode non krisis.…”
Section: Tinjauan Literatur Dan Pengembangan Hipotesisunclassified
“…Mengikuti Gujarati (2004) Campello et al (2011) dan Lian et al (2011 bahwa cash holding perusahaan lebih meningkat saat krisis keuangan terjadi dibandingkan dengan periode non krisis. Hal ini menandakan perusahaan-perusahaan di Indonesia memegang kas lebih banyak saat krisis keuangan global karena motif berjaga-jaga terhadap kondisi perekonomian yang tidak menentu.…”
Section: Pengujian Hipotesisunclassified
“…Research has shown that the effects of financing and risk management differ depending on the economic conditions in particular period (normal periods and crisis periods). Moreover, the empirical studies conducted have attempted to measure the impact of funding shocks on corporate investment by examining the last financial crisis, viewing this as a natural research subject (Campello et al, 2010a;Campello et al, 2010b, Duchin et al, 2010Almeida et al, 2012). These studies have focused on determining the degree to which firms anticipated the financial crisis, showing that, to the extent that firms can forecast an impending crisis, the real effects of financing can be offset before the shock.…”
Section: Introductionmentioning
confidence: 99%
“…Vermoesen, Deloof and Laveren (2013) find qualitatively similar results for a sample of Belgian firms. Furthermore, Campello, Graham and Harvey (2010), and Campello, Giambona, Graham and Harvey (2011) use survey data to show that firms that were financially more constrained were more likely to change their investment plans, while Chodorow-Reich (2014) and Duygan-Bump, 5 Levkov and Montoriol-Garriga (2015) find evidence that credit constrained firms reduced employment after 2007 relative to other firms. Our paper provides additional evidence that the availability of long-term debt is associated with lower firm growth volatility, particularly during the global crisis period.…”
Section: Introductionmentioning
confidence: 99%